The Connection of Money with State Authority in Islamic Law -An Evaluation from Metal to Digital- - Şahin, Nurten Zeliha (Fırat University, 2022)
Money has changed and evolved along with the advancements in technology. The process that started with commodity money has undergone a change and transformation towards more abstract money with digitalization. For this reason, anonymous coins that are not connected to any center and have a unique structure are being talked about today. The most frequently asked question for these decentralized currencies is how a stateless currency can be. How to legally control an area where there is no state monopolizing the legal regulations or how money can perform its functions in such an area has been some of the questions for which the answers are sought. These questions about money are not actually questions that are sought for answers only in this age. In Islamic law, the jurists also asked these questions for the coins in circulation in their own time. In this context, this study aims to evaluate the answers to these questions in terms of how they found answers in Islamic law from past to present. From this point of view, the theory of Islamic law, which reveals the connection of money with the state and social consensus, will also be able to explain the archetype of different perspectives in the approach of Islamic legists and economists towards cryptocurrencies. In this study, while the monetary theory of Islamic law is discussed in the context of historical classical views, it is also evaluated in the context of this theory whether crypto, which is one of the outputs of the decentralized structure created by the digital world, can be qualified as money.

Para, teknolojideki gelişmeler ile birlikte değişmiş ve gelişmiştir. Mal para ile başlayan süreç dijitalleşme ile birlikte daha soyut paralara doğru bir değişim ve dönüşüm geçirmiştir. Bu nedenle bugün için hiçbir merkeze bağlı olmayan anonim ve kendine özgü yapısı olan paralardan konuşulur olmuştur. Merkeziyetsiz yapıdaki bu paralar için en çok sorulan soru ise devletsiz bir paranın nasıl olabileceğidir. Yasal düzenlemeleri tekelinde bulunduran devletin bulunmadığı bir alanın, yasal olarak nasıl denetlenebileceği veya böyle bir alanda paranın fonksiyonlarını nasıl gerçekleştirebileceği, cevabı aranan sorulardan olmuştur. Paraya dair bu sorular aslında bu çağa ait cevabı aranan sorular değildir. İslâm hukukunda fakihler bu soruları kendi zamanlarındaki tedavülde olan paralar için de sormuşlardır. Bu yönü ile bu çalışma bu soruların cevabını İslâm hukuku zemini içinde dünden bugüne nasıl cevap bulduğu noktasında değerlendirmeyi amaçlamaktadır. Bu açıdan bakıldığı zaman İslâm hukukunun paranın devlet ve toplumsal uzlaşı ile bağlantısını ortaya koyan nazariyesi, İslâm hukukçu ve iktisatçılarının kripto paralara yönelik yaklaşımındaki farklı bakış açılarının arketipini de açıklayabilecektir. Bu çalışma, öncelikle İslâm’ın para teorisine ilişkin tarihsel klasik görüşlere odaklanırken, dijital dünyanın ortaya çıkardığı merkeziyetiz yapının çıktılarından birisi olan kriptonun para vasfı kazanıp kazanamayacağı da bu teori bağlamında değerlendirilmiş olacaktır.
İslâm Hukuku’nda Paranın Devlet Otoritesi ile Bağlantısı -Metalden Dijitale Bir Değerlendirme-
Keywords: Religious Studies; Din Araştırmaları